Investigating the origin of cyclical spectral variations in hot, massive stars. Issue Volume 9:Issue S302(2013) (7th August 2014) - David-Uraz, Alexandre; Wade, Gregg A.; Petit, Véronique; ud-Doula, Asif
Abstract: OB stars are known to exhibit various types of wind variability, as detected in their ultraviolet spectra, amongst which are the ubiquitous discrete absorption components (DACs). These features have been associated with large-scale azimuthal structures extending from the base of the wind to its outer regions: corotating interaction regions (CIRs). There are several competing hypotheses as to which physical processes may perturb the star's surface and generate CIRs, including magnetic fields and non radial pulsations (NRPs), the subjects of this paper with a particular emphasis on the former. Although large-scale magnetic fields are ruled out, magnetic spots deserve further investigation, both on the observational and theoretical fronts.